Poverty Alleviation and Long-Term Sustainability of Microfinance Project: With Special Reference to Matale District (International Journal of Management and Sustainability, 2014)
This research is attempted to assess the strengths of poverty alleviation initiatives taken by foreign donors in Sri Lanka. Hence research basically studied the Matale Regional Economic Advancement Project (MREAP) which was funded by the International fund for Agricultural Development (IFAD). Study was based on both primary and the secondary data. Primary data were collected through interviews held with project officers, beneficiaries and other government officers who were involved with various activities in project villages. Descriptive analysis, double difference method, and the regression analysis were the analytical tools used in data analysis. According to the results of the double difference analysis and the descriptive analysis microfinance facility provided by the MREAP has influenced significantly on income levels of the beneficiaries. In general, microfinance has influenced positively on poverty alleviation of beneficiaries. According to the beneficiaries MREAP was a successful project as it provided microfinance for the appropriate businesses during the project implementation period but, neither MREAP nor other government organization have monitored the sustainability of project activities. Analysis of the project reveals that Microfinance is one of the effective tools in poverty alleviation in Sri Lanka and, it is very essential to provide a healthy macroeconomic environment avoiding unnecessary political intervention for the microfinance projects to function effectively and efficiently. This information revels that monitoring of long term sustainability of the activities initiated during the project period after the termination of the project is a vital facto that due attention of relevant authorities should be received.